Effects of dietary docosahexaenoic acid connecting phospholipids on the learning ability and fatty acid composition of the brain - Hiratsuka, S.(Shizuoka-ken. Research Inst. of Fishery, Yaizu (Japan)); Koizumi, K; Ooba, T; Yokogoshi, H (Journal of Nutritional Science and Vitaminology, 2009)
The effects of dietary docosahexaenoic acid (DHA, C22:6n-3) connecting phospholipids on the learning ability and fatty acid composition of the brain were investigated in hypercholesterolemic mice. ICR mice were subjected to a very low level of n-3 fatty acids through two generations. At 4 wk of age, the Fsub(1) generation, n-3 fatty acid deficient male mice were provided with an experimental diet containing four kinds of lipids (safflower oil: Saf, DHA connecting triacylglycerols: DHA-TG, DHA connecting phospholipids: DHA-PL, soybean phospholipids: Soy-PL) for 5 wk. Another group of ICR mice were obtained and fed a commercial diet (CE-2, CLEA Japan, Inc.) as a control. The learning and memory abilities of the mice were evaluated by the modified avoidance procedure. The learning and memory ability level was significantly higher in mice fed the DHA-PL diet than in those fed the Saf and Soy-PL diets, and was the same level as the control. The DHA levels of phosphatidylethanolamine in the brain were significantly higher in the mice fed the two types of DHA-containing diets than in those fed the Saf and Soy-PL diets and was not significantly different between DHA-TG and DHA-PL. The dimethylacetal levels in the brain were significantly higher in the mice fed the DHA-PL diet than in those fed the Saf and DHA-TG diets. These results suggest that the dietary DHA connecting phospholipids have the effect of improving memory learning, and may be related to the both the DHA and plasmalogen levels in the brain.